2010
DOI: 10.4028/www.scientific.net/msf.650.9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Influencing Factors of CO<sub>2</sub> Emissions from Integrated Steelworks Based on LCA

Abstract: The amount of CO2 emissions from steelworks accounts for a great share of the total CO2 emissions from industry in China. Thus, reducing CO2 emissions from steelworks is urgent for China’s environmental protection and sustainable development. This study aims at identifying factors that influence CO2 emissions from steelworks and proposing measures to reduce CO2 emissions. The life cycle inventory (LCI) of iron and steel products implies the relationship between the CO2 emissions of the steelworks and the input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Gao et al analyzed the influence factors of carbon emissions in Inner Mongolia from 2001 to 2010 by using the LMDI model and revealed that the coaldominated energy structure and the fast-growing economy were the main reasons that influenced the carbon emissions [34]. The LMDI technique was used for the carbon increment of Beijing, and results showed that economic activity was the most important factor of carbon emissions growth [35,36]. Chen and Lin used LMDI and Kaya extension methods to analyze the factors of carbon emissions in Tianjin during the period of 2005-2011 and concluded that economic output played a positive role in the increase of carbon emissions, while economic structure, energy intensity of the production sectors, and energy mix of the production sectors played negative roles [37].…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al analyzed the influence factors of carbon emissions in Inner Mongolia from 2001 to 2010 by using the LMDI model and revealed that the coaldominated energy structure and the fast-growing economy were the main reasons that influenced the carbon emissions [34]. The LMDI technique was used for the carbon increment of Beijing, and results showed that economic activity was the most important factor of carbon emissions growth [35,36]. Chen and Lin used LMDI and Kaya extension methods to analyze the factors of carbon emissions in Tianjin during the period of 2005-2011 and concluded that economic output played a positive role in the increase of carbon emissions, while economic structure, energy intensity of the production sectors, and energy mix of the production sectors played negative roles [37].…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, economic development can be associated with carbon dioxide (CO 2 ) emissions, which strengthened carbon (C) input into soils to form SOC [77]. Thus, fast industrial developments in steelwork, mining, metallurgy, and manufacture in Shaoguan emission [54] have tendencies to stimulate local CO 2 [78][79][80]. The negative relationship between GDP and soil TK may result from soil K deficits in regions with highly developed economies.…”
Section: Discussionmentioning
confidence: 99%
“…Here, subscript "g" and "ad" indicates solid and adsorption respectively. However, the adsorption of CO 2 on metals may be dissociation adsorption which is given by; CO 2(g) → C ad + 2O ad ( 2 ) Further investigation is necessary to clarify this point. This result also means that no decomposition of CO 2 occurred during the grinding.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the concentration of the CO 2 gas was increased and this has causes a serious global warming. A lot of methods and technologies, namely introduction of new environmental policy, development of high efficient energy conversion and saving, utilization of renewable carbon free energy source and so on, have been proposed to prevent the global warming from becoming worse [1,2]. One of the technologies against the global warming is the carbon capture and storage (CCS).…”
Section: Introductionmentioning
confidence: 99%